The concept of crimes against road safety and transport operation as a subject of forensic investigation - Danshyn, M. V.; Kolesnik, I. I. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
Based on the analysis of criminal law and forensic literature specifies the subject of forensic investigation in the methodology of the investigation of crimes against traffic safety and operation of transport. It is concluded that the forensic characterization of crimes in this category is significantly different from the characteristics of other types of crime, which are caused by the nature of the objective side of the blanket, when the violation of certain rules is socially dangerous consequences of an accident. It is emphasized that in criminal proceedings the direct knowledge of the original object does not appear actions of certain persons and circumstances of the accident, on the basis of which the conclusions of the violation by certain entities of traffic rules and operation oftransport.